Penerapan Manajemen Halusinasi dengan Teknik Menghardik terhadap Pengendalian Halusinasi Pendengaran pada Pasien Skizofrenia di Ruang Anggrek RSUD Prof. Dr. Margono Soekarjo Purwokerto - Hesti Lutifah Menanda; Ita Apriliyani (Jurnal Ilmu Kesehatan dan Gizi, 2026)
The Application Of Hallucination Management Using The Shutting-Out Technique For The Control Of Auditory Hallucinations In Schizophrenia Patients In The Angruk Ward Of Prof. Dr. Margono Soekarjo General Hospital, Purwokerto. Schizophrenia is a severe mental disorder often accompanied by auditory hallucinations. Auditory hallucinations may cause patients to talk to themselves, appear restless, and experience difficulty in controlling responses to internal stimuli. One non-pharmacological nursing intervention that can be applied is the rebuking technique, a strategy used to firmly reject or dismiss hallucinatory voices. This study aimed to examine the application of the rebuking technique in controlling auditory hallucinations in patients with schizophrenia. This research employed a descriptive case study design using a nursing process approach and was conducted from February 17 to 19, 2026, on a patient diagnosed with schizophrenia experiencing auditory hallucinations. The intervention was implemented over three days, with one session per day lasting approximately 15–20 minutes. The results showed an improvement in the patient’s ability to recognize and control hallucinations, as indicated by a reduction in self-talking behavior, increased awareness of hallucination onset, and the ability to independently apply the rebuking technique. In conclusion, the rebuking technique is an effective nursing intervention to assist patients with schizophrenia in controlling auditory hallucinations.